Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournaments dan Tipe Scramble Terhadap Motivasi dan Hasil Belajar Siswa Kelas XI IPA pada Materi Larutan Asam-Basa di SMAN 1 Bunta - Latupeirisa, Veronica Purnama Sari; Nuryanti, Siti; Mustapa, Kasmudin (Jurnal Akademika Kimia, 2018)
This study aimed to determine the effect of cooperative learning model teams games tournaments and scramble towards the student's motivation and learning outcomes of class XI IPA on the material of acid-base solutions in SMAN 1 Bunta. This research was a pre-experimental with the static pretest-posttest group design. The samples used in the study were students XI IPA 2 (n=30) as a class experiment 1 and students XI IPA 3 (n=28) as an experiment 2. The results of data analysis, the average value of class experiment 1 () was 78.2 and the experimental class 2 () was 73.21. Results of hypotheses testing by statistical t-test two parties it was obtained -ttable ≤tcal≥ + ttable  (tcal = 36.72 for class experiment 1; tcal = 24.65 for class experiment 2  and ttable = 1.67) with a significance level a = 0.05 and degrees of freedom 56, then H0 was rejected and Ha was accepted. The results of the students learning motivation questionnaire showed that the experimental class 1 was the attitude of "strong agree" with the positive category 85.12% and the experimental class 2 was in the attitude of "agree" with the positive category 84.17%. It can be concluded that there is an influence of cooperative learning model teams games tournaments and scramble to the student's motivation and learning outcomes of class XI IPA on the material of acid-base solutions in SMAN 1 Bunta.